Urinary tract infections in patients with type 2 diabetes mellitus: review of prevalence, diagnosis, and management - Nitzan O (Dove Medical Press, 2015)
Orna Nitzan,1–3 Mazen Elias,2,4 Bibiana Chazan,1,2 Walid Saliba2,4 1Infectious Disease Unit, Ha’emek Medical Center, Afula, Israel; 2Bruce Rappaport Faculty of Medicine, Technion–Israel Institute of Technology, Haifa, Israel; 3Infectious Disease Unit, Padeh-Poriya Medical Center, 4Department of Internal Medicine C, Ha’emek Medical Center, Afula, Israel Abstract: Urinary tract infections are more common, more severe, and carry worse outcomes in patients with type 2 diabetes mellitus. They are also more often caused by resistant pathogens. Various impairments in the immune system, poor metabolic control, and incomplete bladder emptying due to autonomic neuropathy may all contribute to the enhanced risk of urinary tract infections in these patients. The new anti-diabetic sodium glucose cotransporter 2 inhibitors have not been found to significantly increase the risk of symptomatic urinary tract infections. Symptoms of urinary tract infection are similar to patients without diabetes, though some patients with diabetic neuropathy may have altered clinical signs. Treatment depends on several factors, including: presence of symptoms, severity of systemic symptoms, if infection is localized in the bladder or also involves the kidney, presence of urologic abnormalities, accompanying metabolic alterations, and renal function. There is no indication to treat diabetic patients with asymptomatic bacteriuria. Further studies are needed to improve the treatment of patients with type 2 diabetes and urinary tract infections. Keywords: diabetes mellitus, diagnosis, management, prevalence, urinary tract infection